Types of Neotropical Pierinae in the collection of Department of Entomology, Natural History Museum, London (Lepidoptera: Pieridae) - Abadjiev, Stanislav P. (Zootaxa, 2006)
A catalog of types of Neotropical Pierinae at the Department of Entomology, Natural History Museum, London, is presented. The collection contains type material of 324 taxa (296 represented by primary types). Each entry includes the species-group name, followed by the generic name, original combination quoted from the original publication, type locality, type specimens as specified with their labels, and notes about current taxonomic status. To increase the stability of nomenclature, and to fix the identity of several species-group names, lectotypes are designated for 116 taxa.